81‐4: Image Quality Evaluation of HDR Displays. Issue 1 (2nd June 2017) - Ye, Zhengnan; Qiu, Jueqin; Xu, Haisong; Luo, M. Ronnier; Westland, Stephen
Abstract : Psychophysical experiments were conducted to investigate the impacting factors on the image quality of HDR displays. The results indicate that the OLED display has advantages over IPS and VA LCDs due to its lower minimum luminance level and less pixel interaction, thus being an appropriate choice to display HDR contents.